Rancang Bangun Aplikasi Mobile Crowdfunding untuk Donasi Sosial Kota Samarinda - Firdaus, Muhammad Bambang; Efendy, Muhammad Yusuf; Prafanto, Anton; Rosmasari, Rosmasari; Suandi, Fadli; Lathifah, Lathifah (JURNAL INTEGRASI, 2024)
Donations are physical gifts made by individuals or legal entities that are given voluntarily and without imbalance. Advances in internet technology are now used to raise social and humanitarian funds and help victims of natural disasters. Crowdfunding takes advantage of this situation, because it uses the internet to generate funds from internet and social media users. This research will look at how to create an Android-based crowdfunding contribution application management system for the Samarinda City area. This study intends to use the Rational Unified Process technique to create an Android-based fundraising application for flood victims, fires of religious buildings, and social institutions in Samarinda City. The main goal is to create software that fits the needs of users. It not only meets system specifications and is usable but also validates whether the system is acceptable. In accordance with the objectives of this study, researchers succeeded in building a donation-raising application for disaster victims, and based on the results of functional testing with the Black Box, the Samarinda City Donation Application has an attractive appearance, the menus available in the application are easy to understand, and the Samarinda City Donation Application this is good enough.